European green capitals: branding, spatial dislocation or catalysts for change?. Issue 1 (2nd January 2020) - Sareen, Siddharth; Grandin, Jakob
ABSTRACT: The European Green Capital (EGC) award has become a familiar feature in a polycentric sustainability governance landscape increasingly characterized by fragmentation and voluntary initiatives. Unclear accountability for translocal connections renders these initiatives at risk of locking unsustainable practices into transitions. Seeking clarity, this paper examines accountability through the lenses of material dislocation and discursive construction in an assessment of Oslo's (2019) and Lisbon's (2020) winning EGC entries. How can the EGC distinction better enable substantive urban sustainability, situating claims within wider energy transitions in these capital regions? Within the award's circumscribed focus on urban centres, do cities account for cognitive and material dislocation through their discursive emphases and telecoupling respectively? Does the EGC catalyse change, brand the capture of low-hanging fruit, or spatially dislocate rather than reduce emissions? We argue that it propagates a focus on optimizing local sustainability effects, while rarely accounting for larger translocal or cross-scalar repercussions. Hence, urban sustainability strategies risk spatially dislocating socio-ecologically unsustainable practices rather than decreasing emissions systemically. Cities need to institute accountability mechanisms that reshape the geographies of responsibility for the systemic and translocal impacts of urban sustainability initiatives, which the EGC could promote by, e.g. including emission indicators for consumption and aviation.